Caminhos cruzados: literatura e pintura, Graciliano Ramos e Cândido Portinari - Oliveira, Larissa Cristina Arruda de (2013)
Graciliano Ramos and Cândido Portinari were friends, but they had something in common that bound most strongly: the desire to express in their works the authentic Brazilian man, the worker and the migrant in their daily lives. This research aims to show how the works of Graciliano and Candido Portinari are close, not only as a social content and theme, but mainly as a form, style and technical resources, as the verbal and visual language are intimately linked as modes of representation. The rapprochement between Graciliano and Cândido Portinari, between the books São Bernardo, Vidas Secas, and the frames Café, Lavrador de café, Retirantes and Criança Morta, aims to demonstrate how the life and work of these artists intersect, in order to represent critically the reality of the time, through a dialectical analysis of form and content, combining text and context in levels of interpretation, according to the hermeneutic proposal of Frederic Jameson in the political unconscious (1982) and the principles of visual semiotics. To achieve this goal, we consider the history of each narrative, structural components, linking them to the historical context of the country at the time. Thus we examine how each represents a social issue: the contradictory reality of Brazil, a country that keeps living archaic modes of production with the arrival of Modernism and Capitalism; antagonistic classes of this society, exploiters and exploited, farmers, migrants, landowners, the government; and alienation/reification that they are submitted, direct consequences of this system. The analyzes are performed with dialectic dialogue, form and content, text and context in reading the social content of his compositions. That is, we analyze how they say what they say about this fundamental aspect of socioeconomic and political organization of the country. Thus, through the analysis we confirm why Graciliano and Portinari are considered realistic and social critics, as such works make use of realism and expressionism as technical resources to bring about awareness of the real and present in the political unconscious subtexts, which allows to conclude from the comparison made that the connection between them, the analogy between literature and painting produced, is stronger and larger than the gap.